2021
DOI: 10.1093/ajcp/aqab111
|View full text |Cite|
|
Sign up to set email alerts
|

Global Cytopathology-Hematopathology Practice Trends

Abstract: Objectives Small-volume biopsy—fine-needle aspiration biopsy (FNAB) with or without core biopsy—is in increasing use in diagnosis and management of lymphoma patients. Our objective was to survey the current practice in small-volume biopsy diagnosis of lymphoma, focusing on the interaction among hematopathologists and cytopathologists and the integration of FNAB, core biopsy, and flow cytometry studies at sign-out. Methods Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Zadeh et al. found that workflow and communication between cytopathology and hematopathology are inconsistent across different institutions, though when communication does occur, pathologists tend to reconsider original diagnoses 63 . The Re‐imagine Cytopathology Task Force has recently suggested that synchronous review and reporting of combined FNA and CNB specimens is superior to review of either alone by allowing for concurrent evaluation of cytology and histology and enabling tissue preservation for optimal ancillary testing triage 64 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zadeh et al. found that workflow and communication between cytopathology and hematopathology are inconsistent across different institutions, though when communication does occur, pathologists tend to reconsider original diagnoses 63 . The Re‐imagine Cytopathology Task Force has recently suggested that synchronous review and reporting of combined FNA and CNB specimens is superior to review of either alone by allowing for concurrent evaluation of cytology and histology and enabling tissue preservation for optimal ancillary testing triage 64 .…”
Section: Discussionmentioning
confidence: 99%
“…The use of FNA as a diagnostic adjunct has also been advocated, both as a means to provide additional material and cytologic assessment to a concurrently obtained CNB and to assist in the decision of whether a CNB should be performed. 63 The Re-imagine Cytopathology Task Force has recently suggested that synchronous review and reporting of combined FNA and CNB specimens is superior to review of either alone by allowing for concurrent evaluation of cytology and histology and enabling tissue preservation for optimal ancillary testing triage. 64 These studies suggest that communication across departments and integrated reporting are key in order to effectively and clearly provide patient biopsy results.…”
Section: Combined Fine-needle Aspiration and Core Needle Biopsymentioning
confidence: 99%
“…This is a retrospective exploratory study, and confounders are numerous, including unknown variations in practice patterns, reasons for repeat biopsy, and limited focus on the evaluation for FL. While this is a multi-institutional study, clinical practice varies between these institutions and could significantly impact the quality of the SVB analysis as well as the decisions to perform a subsequent biopsy across the various clinical scenarios 17. We therefore present cohort data to the pathology and oncology communities as a snapshot of the current state but do not provide P values or statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
“…All institutions included in this study are large academic tertiary referral centers with an interest in hematopathology and/or cytology collaboration and with subspecialized pathologists. A recent study by Zadeh et al 32 . evaluating global practice differences in the evaluation of lymphoma on FNA specimens found that communication between cytopathologists and hematopathologists was inconsistent across different practices and also identified marked differences in access to ancillary testing.…”
Section: Discussionmentioning
confidence: 99%
“…All institutions included in this study are large academic tertiary referral centers with an interest in hematopathology and/or cytology collaboration and with subspecialized pathologists. A recent study by Zadeh et al 32 evaluating global practice differences in the evaluation of lymphoma on FNA specimens found that communication between cytopathologists and hematopathologists was inconsistent across different practices and also identified marked differences in access to ancillary testing. Therefore, the practices and resources available at the institutions participating in this study may differ from those of other clinical settings, and our findings may represent a best-case scenario in terms of expertise and interdepartmental communication.…”
mentioning
confidence: 99%